ผลของโปรแกรมการจัดการกับอาการต่ออาการปวดหลังส่วนล่างของหญิงตั้งครรภ์ - อรทัย สิงห์คำ (จุฬาลงกรณ์มหาวิทยาลัย, 2005)
The purpose of this experimental research was to examine the effect of a symptom management program on low back pain in pregnancy. The conceptual framework of this study was based on the Symptom Management Model (Dodd et al., 2001), and related literature on low back pain in pregnancy. Subjects consisted of 40 pregnant women with low back pain. Subjects were matched by age, height, parity and weigh gain during pregnancy. Subjects were randomly assigned to control or experimental groups using a piece of paper marked "E" and "C", 20 for each group. The control group received routine nursing care while the experimental group received the eight-week symptom management program. The program comprised of five sessions: 1) assessment of symptom experience in pregnant women with low back pain, 2) providing knowledge on management of low back pain in pregnancy, 3) building skills on management of low back pain in pregnancy, 4) management of low back pain at home, and 5) evaluation of low back pain in pregnancy. Visual Analogue Scale (VAS) was used to measure low back pain. The VAS was tested for its internal consistency using a test-retest method. It demonstrated acceptable reliability at .99. A modified version of posture in daily living developed by Darin Tohkani (2002) and pelvic tilt exercise plan developed by the researcher were used to monitor the intervention. Both scales demonstrated valid contents with CVI of 1.0. Data were analyzed using descriptive statistics and t-test. Major findings were as follows: 1. The mean score of low back pain of pregnant women after receiving the symptom management program was significantly lower than before receiving the program (p<.01). 2. The mean score of low back pain of pregnant women in the experimental group receiving the symptom management program was significantly lower than that of the control group (p<.01)